2006
DOI: 10.1021/cb600196w
|View full text |Cite
|
Sign up to set email alerts
|

An ent-Kaurene That Inhibits Mitotic Chromosome Movement and Binds the Kinetochore Protein Ran-Binding Protein 2

Abstract: Using a chemical genetics screen, we have identified ent-15-oxokaurenoic acid (EKA) as a chemical that causes prolonged mitotic arrest at a stage resembling prometaphase. EKA inhibits the association of the mitotic motor protein centromeric protein E with kinetochores and inhibits chromosome movement. Unlike most antimitotic agents, EKA does not inhibit the polymerization or depolymerization of tubulin. To identify EKA-interacting proteins, we used a cell-permeable biotinylated form that retains biological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…For example, the activation of kinesin-1 by RanBP2 mediates adenoviral infection by promoting viral capsid disruption and uncoating at the nuclear pore and outward dispersion of capsid and selective nucleoporins, such as RanBP2 [27]. Collectively, these data support that RanBP2 mediates the tight coordination of pleiotropic motor and energy-driven trafficking processes at distinct cell cycles and between various cell types [24,25,27,88]. Future studies on the physiological effects of RBD 2 , RBD 3 and KBD of RanBP2 with animal models should help to tease out the multi-functional activities associated with the interplay between kinesin-1, Ran GTPase and RanBP2 in mitochondrial motility and other transport events.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the activation of kinesin-1 by RanBP2 mediates adenoviral infection by promoting viral capsid disruption and uncoating at the nuclear pore and outward dispersion of capsid and selective nucleoporins, such as RanBP2 [27]. Collectively, these data support that RanBP2 mediates the tight coordination of pleiotropic motor and energy-driven trafficking processes at distinct cell cycles and between various cell types [24,25,27,88]. Future studies on the physiological effects of RBD 2 , RBD 3 and KBD of RanBP2 with animal models should help to tease out the multi-functional activities associated with the interplay between kinesin-1, Ran GTPase and RanBP2 in mitochondrial motility and other transport events.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in agreement with recently reported activities for other kauranoids such as ent-16b-17a-dihidroxykaurene (Morales et al, 2005), ent-15-oxo-1,7,14,20-tetrahydroxykaur-16-ene or Kamebakaurin (Lee et al, 2002), and ent-16-kaur-16-en-19-oic acid (Castrillo et al, 2001), derivatives from kaura-9(11),16-dien-19-oic acid (Alonso, 2006), among many others, where they are sensitizing the tumoral cells to undergo apoptosis. Rundle et al (2006) recently reported that EOKA (1c) induces mitotic arrest on human epithelial cell lines at early drug exposure times. This group did not find evidence of apoptosis induction; however, other compounds such as mebendazole (methyl 5-benzoyl-2-benzimidazole-carbamate) (Sasaki et al, 2002), or arsenic trioxide (Ling et al, 2002), besides inducing mitotic arrest, also provoked apoptosis in human tumor cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Since each one of these compounds can similarly induce apoptosis, it could be inferred that the enone moiety might be responsible for the biological activity. Moreover, although EOKA (1c) has been proven to cause mitotic arrest by inhibiting RanBP2 function at early drug exposure times (Rundle et al, 2006), the specific mechanisms of action of this compound to unchain apoptosis still remain to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the bulk of the protein is gray, several residues are color-coded: yellow: aa interacting with FK506; red: aa interacting with calcineurin; blue: aa responsible for catalytic activity; orange: aa interacting with FK506 and calcineurin; light green: catalytic aa interacting with FK506; dark green: catalytic aa interacting with calcineurin and FK506. Images were made in PyMOL (DeLano Scientific LLC, Palo Alto, CA, USA) based on PDB ID: 1TCO [161] [198,199] Human parvulins 1 Pin1 Nuclear 1 WW Cell cycle regulation [200,201] [63]…”
Section: Cyclosporin and Cyclophilinsmentioning
confidence: 99%